Understanding the residents' social impact perceptions of an African Cultural Festival: the case of Macufe. Issue 2 (4th March 2019) - Scholtz, Marco; Viviers, Pierre-Andre; Maputsoe, Limpho
ABSTRACT: The Macufe is one of the Africa's largest cultural festivals, and takes place annually in Bloemfontein, South Africa. This 10-day event attracts approximately 140, 000 attendees, meaning that the residents have to share facilities and services with tourists. The effects of such interactions can be both positive and negative. Community members are stakeholders in any tourism ventures that take place in their area, meaning that their goodwill is of utmost importance. Therefore, the social impacts of this event should be well managed to foster community support. For this reason, a quantitative study was done to determine residents' social impact perceptions towards the event. A total of 425 questionnaires were completed by willing residents who lived in proximity to festival activities. From an exploratory factor analysis, four factors were extracted, namely community enhancement, community degradation, tourism growth and increased public spending and interaction. It was found that the event does not generate significant levels of positive social impacts, and that the negative social impacts are viewed almost equal to the positive social impacts. This was one of the first social impact perception studies done on an African arts festival, which contributes to the sustainable management of such crucial events.